Can a chatbot enhance hazard awareness in the construction industry? - Zhu, Xiaoe; Li, Rita Yi Man; Crabbe, M. James C.; Sukpascharoen, Khunanan (Frontiers in Public Health, 2022)
Safety training enhances hazard awareness in the construction industry. Its effectiveness is a component of occupational safety and health. While face-to-face safety training has dominated in the past, the frequent lockdowns during COVID-19 have led us to rethink new solutions. A chatbot is messaging software that allows people to interact, obtain answers, handle sales and inquiries through a computer algorithm. While chatbots have been used for language education, no study has investigated their usefulness for hazard awareness enhancement after chatbot training. In this regard, we developed four Telegram chatbots for construction safety training and designed the experiment as the treatment factor. Previous researchers utilized eye-tracking in the laboratory for construction safety research; most have adopted it for qualitative analyses such as heat maps or gaze plots to study visual paths or search strategies via eye-trackers, which only get the impact of one factor. Our research has utilized an artificial intelligence-based eye-tracking tool. As hazard awareness can be affected by several factors, we filled this research void using 2-way interaction terms via the design of experiment (DOE) model. We designed an eye-tracking experiment to study the impact of site experience, Telegram chatbot safety training, and task complexity on hazard awareness, which is the first of its kind. The results showed that telegram chatbot training enhanced the hazard awareness of participants with less onsite experience and less complex scenarios. Low-cost chatbot safety training could improve site workers’ danger awareness, but the design needs to be adjusted according to participants’ experience. Our results offer insights to construction safety managers in safety knowledge sharing and safety training.